2012
DOI: 10.1007/s11547-012-0831-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor magnetic resonance imaging of the normal breast: reproducibility of DTI-derived fractional anisotropy and apparent diffusion coefficient at 3.0 T

Abstract: ADC and FA measurements obtained with DTI are reproducible and may be valid, reliable and sensitive to change. ADC values obtained with DTI are more reproducible than FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…More recently, diffusion weighted MRI and the resulting maps of apparent diffusion coefficient (ADC) have been evaluated as a complement method to DCE-MRI and it was shown that ADC values can help distinguish between cancers, benign lesions and normal breast tissue 9,10 . In addition, studies of breast diffusion tensor imaging (DTI) were initiated in healthy volunteers and patients with breast lesions at field strength of 1.5 T [11][12][13][14][15] and of 3 T [16][17][18][19][20][21][22][23][24] . Most of these studies reported ADC and fractional anisotropy (FA) values 11,12,14,15,[20][21][22][23] and found these two parameters to be reproducible with ADC values more reproducible than FA 13,20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, diffusion weighted MRI and the resulting maps of apparent diffusion coefficient (ADC) have been evaluated as a complement method to DCE-MRI and it was shown that ADC values can help distinguish between cancers, benign lesions and normal breast tissue 9,10 . In addition, studies of breast diffusion tensor imaging (DTI) were initiated in healthy volunteers and patients with breast lesions at field strength of 1.5 T [11][12][13][14][15] and of 3 T [16][17][18][19][20][21][22][23][24] . Most of these studies reported ADC and fractional anisotropy (FA) values 11,12,14,15,[20][21][22][23] and found these two parameters to be reproducible with ADC values more reproducible than FA 13,20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies of breast diffusion tensor imaging (DTI) were initiated in healthy volunteers and patients with breast lesions at field strength of 1.5 T [11][12][13][14][15] and of 3 T [16][17][18][19][20][21][22][23][24] . Most of these studies reported ADC and fractional anisotropy (FA) values 11,12,14,15,[20][21][22][23] and found these two parameters to be reproducible with ADC values more reproducible than FA 13,20 . The results of these studies indicated that malignant lesions exhibit low ADC values as compared to normal tissue and benign lesions, however, conflicting results were reported on the values and diagnostic capability of FA 11,12,14,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, DTI measurement of the normal breast has allowed characterizing the breast ductal/ glandular trees. [16][17][18][19] Blockage of the ducts and lobules by cancer cells increases the extracellular tortuosity and restriction of the water movement, causing a reduction of the diffusion coefficients in all directions and consequently also decreasing the diffusion anisotropy. 20 In most breast DTI studies, FA has been the common anisotropy index applied for both characterization of the normal fibroglandular tissue 16,17,[21][22][23] and for cancer diagnosis.…”
mentioning
confidence: 99%
“…7,[10][11][12] Some studies have highlighted its high reproducibility and feasibility in the clinical setting. 13,14 For example, reproducibility studies in brachial plexus show an overall reproducibility between 81% and 92%, considering combined influence of the observer and of the repeated measurements.…”
Section: Discussionmentioning
confidence: 99%